2018
DOI: 10.1007/s13765-018-0362-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating natural compounds as potential insecticides against three economically important pests, Bemisia tabaci (Hemiptera: Aleyrodidae), Frankliniella occidentalis (Thysanoptera: Thripidae), and Myzus persicae (Hemiptera: Aphididae), on greenhouse sweet peppers

Abstract: Sweet pepper (Capsicum annuum L.) is one of the major export crops in the Republic of Korea. Currently, synthetic insecticides are frequently used to control major greenhouse pests including Bemisia tabaci (Hemiptera: Aleyrodidae), Myzus persicae (Hemiptera: Aphididae), and Frankliniella occidentalis (Thysanoptera: Thripidae) in Korea. However, the repeated use of chemicals has caused insecticide resistance to be developed by pests. Therefore, there is a growing demand to develop biopesticides that have high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Consistent with the effect of cPTIO treatment, silencing of NOA1 significantly decreased the production of NO, thus enhancing tobacco's resistance to B. tabaci. In line with our results, B. tabaci performance is somewhat increased in sweet pepper after the application of NO aqueous solution (Kim et al, 2018). Wünsche et al (2011a) found that the irNaNOA1 tobacco plants with lower NO contents are more resistant to M. sexta (Wünsche et al, 2011a).…”
Section: No Signaling Is Positively Correlated With B Tabaci Performsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the effect of cPTIO treatment, silencing of NOA1 significantly decreased the production of NO, thus enhancing tobacco's resistance to B. tabaci. In line with our results, B. tabaci performance is somewhat increased in sweet pepper after the application of NO aqueous solution (Kim et al, 2018). Wünsche et al (2011a) found that the irNaNOA1 tobacco plants with lower NO contents are more resistant to M. sexta (Wünsche et al, 2011a).…”
Section: No Signaling Is Positively Correlated With B Tabaci Performsupporting
confidence: 89%
“…As a crucial signaling molecule, NO has been associated with the induced plant defensive response to phloem feeder stress. For instance, foliar treatment with NO donors induced defense reactions against the pea aphid, A. pisum, and the green peach aphid, M. persicae, in pea and sweet pepper plants (Woźniak et al, 2017;Kim et al, 2018). In our bioassay, exogenous NO donor SNP treatment significantly increased the oviposition preference of whitefly adults and accelerated the nymphal development in tobacco plants.…”
Section: No Signaling Is Positively Correlated With B Tabaci Performmentioning
confidence: 61%
“…Previous studies have shown that fluorescent marking does not negatively affect multiple organisms . However, caution is warranted when applying this method to different organisms as chemical application may have distinct effects . Indeed, Reid and Reid have found that fluorescent marking can induce a faster mass loss in Dendroctonus ponderosae (Coleoptera: Curculionidae) compared to unmarked individuals.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,31 Nevertheless, although the results by Rice et al 33 suggest the effectiveness of a handheld laser among the other detection devices on fluorescent-marked insects, whether the method was viable in detecting living insects, especially Riptortus pedestris, was not provided because the experiment was conducted with dead H. halys samples. The response of insects to chemicals may vary respective of the compounds and the application method, 49 and likewise, the effect of the fluorescent marking on a living organism varies with the species of the insect and the method used to mark the insect. However, the effect of the spraying method on Riptortus pedestris was not tested previously.…”
Section: Discussionmentioning
confidence: 99%